Hepatic SIRT3 Upregulation in Response to Chronic Alcohol Consumption Contributes to Alcoholic Liver Disease in Mice - Ma, Yue; Chai, Hui; Ding, Qinchao; Qian, Qianyu; Yan, Zhaoyuan; Ding, Bin; Dou, Xiaobing; Li, Songtao (Frontiers in Physiology, 2019)
Background: Alcoholic liver disease is a type of chronic liver diseases caused by chronic ethanol overconsumption. The pathogenesis of alcoholic liver disease is complex and there is no effective clinical treatment so far. SIRT3 is an NAD+-dependent deacetylase primarily located inside mitochondria, the reports on the effect of chronic alcohol exposure on liver SIRT3 expression are scarce. The study aims to investigate the effect of chronic alcohol consumption on hepatic SIRT3 expression and its role in alcoholic-induced liver injury. Methods: Using Lieber-DeCarli mouse model of alcoholic liver disease, we analyzed the regulation of SIRT3 and the effect of liver-specific knocking-down of SIRT3 on alcohol-induced liver injury. HepG2 and AML12 hepatocytes were employed to detect the biological function of SIRT3 on alcohol-induced hepatic cytotoxicity and its potential mechanism. Results: Chronic alcohol exposure led to hepatic SIRT3 upregulation and liver-specific SIRT3 knockdown alleviated alcoholic feeding-induced liver injury and lipids accumulation, which is associated with improved autophagy induction. Additionally, autophagy induction contributed to the cytoprotective effect of SIRT3 knockdown on ethanol-induced hepatocyte cell death. Conclusion: In summary, our data suggest that hepatic SIRT3 upregulation in response to chronic alcohol exposure and liver-specific SIRT3 knockdown induced autophagy activation further alleviating alcoholic-induced liver injury, which represents a novel mechanism in this process.